Study of factors associated with obesity in patients using antipsychotics in schizophrenia - Vishalakshi Patnam; P Ramya Keerthi; P Ravi Kiran; Dinesh Panati (Telangana Journal of Psychiatry)
Background: The atypical antipsychotic agents can raise body weight directly by acting on feeding areas of the brain, or indirectly by endocrine effects such as decreased gonadal levels, hyperprolactinemia, and hypercortisolism, and effect on peptide hormones, especially leptin. This may provide inputs from a mental health prevention and promotion standpoint. It may inform the development of prediction tools and better interventions. It may also encourage research on the causal pathways and mechanisms mediating the relationship. Aims and Objectives: To study the factors associated with obesity in patients with schizophrenia using antipsychotics. To compare sociodemographic profile, duration of illness in patients with schizophrenia to obesity and associated risk factors. Subjects and Methods: One hundred patients diagnosed with Schizophrenia according to the International Classification of Diseases-10 were selected, and informed consent was obtained. Weight, height, waist circumference, body mass index, lipid profile, i.e., total cholesterol (TC), triglyceride (TG), high-density lipoprotein (HDL) cholesterol, and low-density lipoprotein (LDL) cholesterol of the patients were measured using standard scales and kit. Results: The mean fasting blood sugar level in cases was 33.3 ± 24.2. The mean TC levels were 176.2 ± 15.8. The mean TG levels were 123.4 ± 15.1. The mean HDL levels were 47 ± 6.1. The mean LDL levels were 103.3 ± 15.9. and decreased ratio of LDL/HDL in responders taking atypical antipsychotic drugs (n = 32), but not in patients treated with conventional antipsychotic drugs (n = 36). The weight gain after a typical antipsychotic drug, i.e., haloperidol, was 64.8 ± 7.5. The weight gain after atypical antipsychotic medication, i.e., olanzapine, was 65.0 ± 7.5, risperidone was 64.5 ± 7.2, and remaining olanzapine and risperidone were 65.1 ± 7.6, respectively. Conclusion: With steadily increasing rates of obesity globally, an understanding of the impact of obesity on the prevalence rates of mental disorders assumes significance. It may inform the development of prediction tools and better intervention. Further, obesity has been identified consistently as a risk factor for metabolic syndrome among psychiatric populations receiving treatment with agents such as olanzapine and risperidone. This three-way link between obesity, metabolic syndrome, and psychiatric disorders presents significant opportunities to improve our understanding of the pathogenesis of psychiatric disorders and develop newer therapeutic targets.